The Expansion Of Emotional Jurisdiction In Viral Digital Courtrooms and Its Impact On Judicial Legitimacy - Yohanna YR Watofa; Atang Suryana; Nurjanah Lahangatubun (CV Putra Publisher, 2026)
The rise of social media has created viral digital courtrooms, namely online spaces where legal cases are discussed, judged, and emotionally interpreted by the public outside formal court procedures. This phenomenon expands emotional jurisdiction, understood as the growing influence of public emotions on the social perception of legal authority, fairness, and judicial credibility. This study analyzes how emotional dynamics in viral digital courtrooms affect judicial legitimacy. Using a socio-legal qualitative approach, the study applies digital discourse analysis to 150 social media posts, online comments, digital news reports, and three viral legal cases. The analysis is supported by in-depth interviews with 12 informants, including legal academics, media observers, and active social media users. The data were examined through thematic analysis and critical discourse analysis. The findings show that viral digital courtrooms intensify public emotional participation and create parallel public judgments that shape perceptions of judge neutrality, procedural fairness, and institutional credibility. The study concludes that judicial legitimacy in the social media era requires more adaptive legal communication and stronger digital governance strategies.